Dosimetric verification of compensated beams using radiographic film - Jurković, Slaven (Radiology and oncology (Ljubljana), 2011)
Introduction. External photon beam modulation using compensators in order to achieve a desired dose distribution when brachytherapy treatment is followed by external beam radiation is a well-established technique. A compensator modulates the central part of the beam, and the dose beneath the thickest partof the compensator is delivered mostly by scattered, low energy photons. Atwo-dimensional detector with a good spatial resolution is needed for the verification of those beams. In this work, the influence of different types ofdetectors on the measured modulated dose distributions was examined. Materials and methods. Dosimetric verification was performed using X-Omat V, Eastman Kodak radiographic films at different depths in a solid water phantom.The film measurements were compared with those made by ionization chambers. Photon beams were also modelled using EGSnrc Monte Carlo algorithm to explain the measured results. Results. Monte Carlo calculated over-responseof the film under the thickest part of the compensator was over 15%, which was confirmed by measurements. The magnitude of over-response couldbe associated with changes in the spectra of photon energy in the beam. Conclusions. The radiographic film can be used for the dosimetry of compensated high energy photon beams, with limitations in volumes where photonspectra are hardly degraded.
Keywords: Brachytherapy; Brahiterapija; Film Dosimetry; Film, dozimetrija; Fotoni; Methods; Monte Carlo Method; Monte Carlo, metoda; Photons; Radioterapija; Radioterapija, doziranje; Radiotherapy; Radiotherapy Dosage